Sentido y significados de docentes de básica y media académica acerca del interrogante ¿Para qué le hace usted preguntas al estudiante durante la clase? (2020)
The research is focused on knowing, from the inclusive critical approach of pedagogy, what is the meaning and significance that teachers in the municipality of Chimá-Córdoba in Colombia have about the question: Why do you ask the student questions during class? The questions that teachers ask in class or outside it in an educational institution have a meaning and significance for every teacher, which is a way of developing thinking in the classroom. The pedagogy of the question and its practice allows the teacher to find situations that indicate to him/her the state in which the students are. The reflection made on the students' previous interests when being questioned through the pedagogical question can have a problematic, open, inquiring, reflexive, technical, and/or any other connotation that provides the teacher with a diagnosis on the level of learning and the development of critical thinking; furthermore, to know how the consultations, and/or the process of axiological formation are going. The methodology was approached from the qualitative design inspired by the interpretative paradigm or vertehen, of the narrative-interpretative type. An intentional sample was used, with the aim of being able to move towards a deliberate sampling throughout the study, based on the information needs detected in the first results. Among the findings, it was found that teachers apply a greater percentage of traditional conceptions of self and heterostructuralist teaching than from a socio-cognitivist perspective.